EARTH REMOTE SENSING DATA IN STUDYING ICE COVER FORMATION AND ANALYZING ITS REGIME ON LAKE SEVAN, ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
One of the important characteristics of the thermal regime of lakes is the ice regime, which affects the entire lake ecosystem. At present, remote sensing methods, in particular the NDSII spectral index, allow to observe the ice cover, map it and carry out its cartometric studies. The purpose of this study is to assess the possibility of using satellite remote sensing data for analyzing the ice cover of Lake Sevan and studying its ice regime. The remote sensing data of Lake Sevan confirm the increase in the frequency of its freezing as a result of lake water level decrease. Analysis of the results of Lake Sevan ice cover mapping showed that NDSII>0.5 corresponds to complete freezing of the lake.  As a result of application of remote sensing data, both the possibility and necessity of their use for studying the ice cover and ice regime of Lake Sevan were revealed and confirmed.
Keywords: Lake Sevan; ice cover; remote sensing data; NDSII